PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT ISLAM SITI AISYAH MADIUN - Alfian Nor Ichsan; Ahmad Setiono (University of Darussalam Gontor, 2020)
Based on the employee attendance data of Siti Aisyah Madiun Islamic Hospital in July to December 2018, it can be concluded that employee discipline is said to be good, this is evident from the absence of employee attendance at a low level. This study aims to determine whether there is an influence of the work discipline applied by Siti Aisyah Madiun Islamic Hospital on employee performance. This type of research is quantitative research where the data to be examined is presented in the form of questionnaires distributed to respondents and will then be processed using the SPSS 23 tool to find research results. The population in this study was 358 with a sample of 72 employees of the Islamic Hospital of Siti Aisyah Madiun, the sample was taken using a simple random sampling technique. The value measurement technique used in this study is a Likert scale. To test the independent variable whether it influences the dependent variable, the writer uses several analytical techniques, including: Classical Assumption Test and Simple Linear Regression Analysis. The results of this study indicate that R2 (R square) is obtained at 0.840. Then the value of 0.840 x 100%, the contribution of the influence of Work Discipline (X) on Employee Performance (Y) at the Islamic Hospital of Siti Aisyah Madiun was 84% while the remaining 16% was influenced by other factors not examined in this study.